The effect of different feed formulation on nutritional related blood profile in goat - Daud, Nur Hafizatul Aiezzah (2016)
Poor animal health and disease are usually related to the cause of low farm productivity level and indirectly to low profit margin. Good feeding strategies should be designed and implemented in order to improve the herd health thus increase farm performance. Adequate nutrient should be given to animal according to their production stages in order to meet the nutrient requirement. Determining the nutritionally related blood metabolite was used as an indicator of nutritional status.Thus, this study was conducted to determine the nutrient composition of different feed formulation and the effect of different feed formulation on nutritional related blood profile in goat. Eighteen female adult goats, Capra aegagrus hircus (Boer cross) were selected and allocated into three different groups (n=6) and assigned according to their different formulation (Diet 1; current fed by the farmer, Diet 2; maintenance diet and Diet 3; flushing diet). Blood sampling were conducted before and after fourth weeks of feeding trial and analysed for selected parameters by using SPSS software. Proximate analysis of diets was done and revealed comparable value of Crude Protein and Crude Fat. Glucose, Total Protein and Calcium level showed significant difference between groups (p-value< 0.05) while Cholesterol and Fatty Acid showed no significant difference (p-value>0.05). Fatty Acid analysis of feed and plasma showed Polyunsaturated Fatty Acid is higher than Satureated Fatty Acid. Overall, Diet 3 shows the highest value of all blood parameters analysed in this study. Hence, it is very important to provide animal with nutrient according to production stages as sufficent protein and energy will improve the animal performance in terms breeding efficacy and quality of animal products.This study indicates that different feed formulation does affect on certain nutritional related blood profile in goat.